Screening and Identification of Potential Biomarkers in Hepatitis B Virus-Related Hepatocellular Carcinoma by Bioinformatics Analysis - Zeng, Xian-Chang; Zhang, Lu; Liao, Wen-Jun; Ao, Lu; Lin, Ze-Man; Kang, Wen; Chen, Wan-Nan; Lin, Xu (Frontiers in Genetics, 2020)
Hepatocellular carcinoma (HCC) is one of the top killer cancers globally. Hepatitis B virus (HBV) infection might cause chronic hepatitis and cirrhosis, leading to HCC. To screen the prognostic genes and therapeutic targets for HCC by bioinformatics analysis and determine the underlying mechanisms of HBV-related HCC, three high-throughput RNA sequencing-based raw datasets, namely GSE25599, GSE77509, and GSE94660, were obtained from the Gene Expression Omnibus and one RNA-seq raw dataset was acquired from The Cancer Genome Atlas (TCGA). 103 up-regulated and 127 down-regulated genes were identified, and a protein-protein interaction (PPI) network was established using Cytoscape software. Twelve pivotal genes were selected as hub genes. The 230 differentially expressed genes and 12 hub genes were subjected to functional and pathway enrichment analyses, and the results suggested that cell cycle, nuclear division, mitotic nuclear division, oocyte meiosis, retinol metabolism, and p53 signaling-related pathways play important roles in HBV-related HCC progression. Further, among the 12 hub genes, KIF11, TPX2, KIF20A and CCNB2 were identified as independent prognostic genes by survival analysis and univariate and multivariate Cox regression analysis. These four genes have higher expression in the HCC than in the normal tissue samples, as indicated in the Oncomine, a cancer-profiling database containing all of the published differential gene expression analyses. Also, comparing with normal tissues, expression of KIF11, TPX2, KIF20A and CCNB2 have higher expression levels in the HBV-related HCC than in the HCV-related HCC tissues. In conclusion, our results suggest that KIF11, TPX2, KIF20A and CCNB2 might be involved in the carcinogenesis and development of HBV-related HCC. They can thus be used as independent prognostic genes and novel biomarkers for the diagnosis and development of therapeutic strategies for the HBV-related HCC.